2019
DOI: 10.3390/cancers11030402
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Targetable Lesions in Anaplastic Thyroid Cancer by Genome Profiling

Abstract: Anaplastic thyroid cancer (ATC) is a rare and extremely malignant tumor with no available cure. The genetic landscape of this malignancy has not yet been fully explored. In this study, we performed whole exome sequencing and the RNA-sequencing of fourteen cases of ATC to delineate copy number changes, fusion gene events, and somatic mutations. A high frequency of genomic amplifications was seen, including 29% of cases having amplification of CCNE1 and 9% of CDK6; these events may be targetable by cyclin depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 59 publications
4
39
0
Order By: Relevance
“…In regards to DNA methylation, the majority of differentially methylated CpGs in ATC were hypomethylated and in intergenic regions (Figure 2), in line with previous studies [10,11,24]. Global hypomethylation is a common phenomenon in cancer and is believed to be associated with genomic instability [25], agreeing well with the genomic complexity generally seen in ATC [20]. Conversely, most hypermethylated CpG sites were in CpG islands, indicating specific effects on gene expression.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In regards to DNA methylation, the majority of differentially methylated CpGs in ATC were hypomethylated and in intergenic regions (Figure 2), in line with previous studies [10,11,24]. Global hypomethylation is a common phenomenon in cancer and is believed to be associated with genomic instability [25], agreeing well with the genomic complexity generally seen in ATC [20]. Conversely, most hypermethylated CpG sites were in CpG islands, indicating specific effects on gene expression.…”
Section: Discussionsupporting
confidence: 88%
“…In cancer, TWIST1 has been shown to be involved in epithelial-mesenchymal transition and to promote metastasis [35]. Notably, we have previously reported that TWIST1 is sometimes amplified in primary ATC (#2 in the present study) [20]. Thus, aberrant activation of TWIST1-associated pathways, either by copy number changes or by aberrant methylation, could be a recurrent event in ATC.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations